Morphological variation among late holocene Mexicans: Implications for discussions about the human occupation of the Americas. Issue 1 (20th February 2017) - Herrera, Brianne; Peart, Daniel; Hernandez, Nicole; Spradley, Kate; Hubbe, Mark
Abstract: Objectives: Cranial morphology has previously been used to estimate phylogenetic relationships among populations, and has been an important tool in the reconstruction of ancient human dispersals across the planet. In the Americas, previous morphological studies support a scenario of people entering the Americas and dispersing from North America into South America through Meso America, making the Mexican territory the natural funnel through which biological diversity entered South America. Materials and methods: We explore the cranial morphological affinities of three late Holocene Mexican series, in relation to ancient and modern crania from North and South America, Australo‐Melanesia, and East Asia. Morphological affinities were assessed through Mahalanobis Distances, and represented via Multidimensional Scaling and Ward's Linkage Cluster analysis. Minimum F ST values were also calculated for each series. Results: Our results show Mexican groups share morphological affinities with the Native American series, but do not cluster together as would be expected. The minimum F ST estimates show between‐group variation in the Americas is higher than the Asian or Australo‐Melanesian populations, and that Mexican series have high between‐group variance ( F ST  = 0.124), compared to the geographically larger South America ( F ST  = 0.116) and North America ( F ST  = 0.076). Discussion: These results show that the Mexican series share morphological affinities with the East Asian series, but maintains high levels of between‐group variation, similar to South America. This supports the suggestion that the high phenotypic variation seen the Americas is not a result of its size, as it can be found in more constricted areas, such as the Mexican territory.